2010
DOI: 10.1093/ije/dyq084
|View full text |Cite
|
Sign up to set email alerts
|

The BEACHES Study: health effects and exposures from non-point source microbial contaminants in subtropical recreational marine waters

Abstract: This study indicated that bathers may be at increased risk of several illnesses relative to non-bathers, even in the absence of any known source of domestic sewage impacting the recreational marine waters. There was no dose-response relationship between gastroenteritis and increasing exposure to enterococci, even though many current water-monitoring standards use gastroenteritis as the major outcome illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 25 publications
4
103
0
3
Order By: Relevance
“…Little was known about the relationship of enterococci and other FIB to human health in recreational waters contaminated by nonpoint sources when the regulations were promulgated (115). Recently, some studies found an association between densities of enterococci and illness rates at beaches impacted by nonpoint sources of contamination (104,304). While there was an increased incidence of gastrointestinal illness, respiratory illness, and skin illness in bathers in one study (104), the only health effect with a dose-response relationship to concentrations of indicator bacteria in both studies was skin illnesses (104,304).…”
Section: Use Of Enterococci As Fecal Indicator Bacteriamentioning
confidence: 96%
See 1 more Smart Citation
“…Little was known about the relationship of enterococci and other FIB to human health in recreational waters contaminated by nonpoint sources when the regulations were promulgated (115). Recently, some studies found an association between densities of enterococci and illness rates at beaches impacted by nonpoint sources of contamination (104,304). While there was an increased incidence of gastrointestinal illness, respiratory illness, and skin illness in bathers in one study (104), the only health effect with a dose-response relationship to concentrations of indicator bacteria in both studies was skin illnesses (104,304).…”
Section: Use Of Enterococci As Fecal Indicator Bacteriamentioning
confidence: 96%
“…Recently, some studies found an association between densities of enterococci and illness rates at beaches impacted by nonpoint sources of contamination (104,304). While there was an increased incidence of gastrointestinal illness, respiratory illness, and skin illness in bathers in one study (104), the only health effect with a dose-response relationship to concentrations of indicator bacteria in both studies was skin illnesses (104,304). Furthermore, in a comparison of analytical methods, the dose-response relationship for skin illness was seen only with samples analyzed by membrane filtration (304).…”
Section: Use Of Enterococci As Fecal Indicator Bacteriamentioning
confidence: 99%
“…Numerous studies have shown that beach sand may serve as a reservoir for pathogens harmful to human health and indicator microbes that can be released into surrounding waters through tidal action or run-off (Alm et al, 2003;Whitman and Nevers, 2003;Boehm and Weisberg, 2005;Beversdorf et al, 2007;Colford et al, 2007;Fleisher et al, 2010;Ge et al, 2010;Sinigalliano et al, 2010;Abdelzaher et al, 2010). Several authors have reported that both indicator bacteria and potential pathogens occur in beach sands of both freshwater and marine environments (Sanchez et al, 1986;Ghinsberg et al, 1994Ghinsberg et al, , 1995Obiri-Danso and Jones, 2000;Desmarais et al, 2002;Sato et al, 2005;Vantarakis et al, 2005;Beversdorf et al, 2007;Bonilla et al, 2007;Vogel et al, 2007;Hartz et al, 2008;Abdelzaher et al, 2010).…”
Section: Bacteriamentioning
confidence: 99%
“…Recent waterbody closures at Brazilian Olympic venues 4 and Waikiki beach, Hawaii 5 illustrate recreational water contamination's public health and economic reach. Several cohort studies and randomized trials have measured swimming-related health risks and risks associated with exposure to waters containing elevated fecal indicator bacteria levels, [6][7][8][9][10][11][12][13][14][15][16][17] but individual studies are usually too small to estimate the public health burden associated with water exposure with respect to missed daily activities (work, school, vacation) or medical visits and hospitalizations that result from gastroenteritis. Moreover, individual studies have not typically enrolled enough swimmers to estimate risks separately for children.…”
mentioning
confidence: 99%